Obstructive Sleep Apnea Syndrome - Predictive Indicators of Severity. (24th June 2020) - Castro, J; Silva, H; Coelho, P; Pereira, T
Abstract: Introduction Obstructive Sleep Apnea Syndrome (OSAS) is a public health issue, due to its increasing prevalence and associated morbidity and mortality, worsened by the underestimated diagnosis of this entity in clinical practice. Objectives To correlate clinical, demographic and anthropometric indicators, and elaborate a predictive equation for OSAS severity and prevalence, in males and females. Methodology In this cross-sectional study, all the included patients performed a type I Polysomnography in ULSM – HPH Neurophysiology Laboratory, between July 2011 and December 2017. Patient's weight, height, body mass index (BMI), waist circumference (WC) and neck circumference (NC) were assessed. Daytime excessive sleepiness was rated through the Epworth Sleepiness Scale (ESS). The apnea-hypopnea index and the snoring presence were obtained through the polygraphic recording. Demographic, anthropometric, clinical variables and ESS punctuation were correlated with the presence of OSAS and its severity through a multivariable regression model. Results The study included 472 patients (275 males and 197 females). OSAS prevalence was 65, 7% (75, 3% in males and 52, 3% in females), being the males related to the most severe forms of OSAS (p < 0, 001), the same happening with the age group 60-69 years. OSAS severity correlated directly with NC, WC, BMI and ESS increase. Snoring was present in 92, 8% of the cases and did not correlate with OSAS severity. In females, severity correlated directly with age and BMI. Age and NC were identified as the strongest independent OSAS predictors (p-value=0, 011 and p-value=0, 006, respectively). Conclusion In this study, OSAS severity predictors were gender, age, NC, WC, BMI, snoring and ESS result (NC and age were the strongest independent predictors). These findings should be confirmed in more robust studies, to identify patients at risk of severe OSAS, to allow earlier diagnostic evaluation and therefore preventing OSAS associated complications.